2019
DOI: 10.1038/s41598-019-39200-7
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of miRNAs by Snail during epithelial-to-mesenchymal transition in HT29 colon cancer cells

Abstract: Epithelial-to-mesenchymal transition (EMT) in cancer cells, represents early stages of metastasisand is a promising target in colorectal cancer (CRC) therapy. There have been many attempts to identify markers and key pathways induced throughout EMT but the process is complex and depends on the cancer type and tumour microenvironment. Here we used the colon cancer cell line HT29, which stably overexpressed Snail, the key transcription factor in early EMT, as a model for colorectal adenocarcinoma cells with a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 53 publications
1
35
0
Order By: Relevance
“…Our previous studies showed that Snail, an early regulator of EMT, affects human HT29 CRC cells transcriptome and miRNA profile and changes HT29 cells phenotype to a promigratory one [9,10]. In this paper, we described Snail effect on mouse CRC line MC38 in order to characterize it before moving to in vivo mouse models of colon cancer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous studies showed that Snail, an early regulator of EMT, affects human HT29 CRC cells transcriptome and miRNA profile and changes HT29 cells phenotype to a promigratory one [9,10]. In this paper, we described Snail effect on mouse CRC line MC38 in order to characterize it before moving to in vivo mouse models of colon cancer.…”
Section: Discussionmentioning
confidence: 99%
“…EV fractions were obtained after sequential centrifugations and ultracentrifugation for 1.5 h at 100,000× g and followed by washing in PBS and another ultracentrifugation. The final EV pellets were resuspended in PBS and stored at −80 • C until use ( [10] and modified from [34]). We submitted all relevant data of our experiments to the EV-TRACK knowledgebase (EV-TRACK ID: EV190098) [35].…”
Section: Isolation Of Extracellular Vesicles From Conditioned Mediamentioning
confidence: 99%
See 1 more Smart Citation
“…MiR-194 is involved in EMT induction and invasion in CRC cell lines [135]; nevertheless, its downregulation in CRC tissue compared to adjacent non-cancerous tissue and its association with inhibition of cell proliferation via regulation of the MAP4K4/c-Jun/MDM2 signaling pathway indicate tumor suppressive features of miR-194 [136]. It has been reported that the miR-194 promoter has a binding site for Snail which leads to miR-194 downregulation and THBS1 upregulation in snail-mediated EMT in HT-29 cells [137]. THBS1 (thrombospondin 1) is an intrinsic inhibitor of angiogenesis which also has a suppressive effect on CRC proliferation and migration.…”
Section: Pro-angiogenic Mirnas In Crcmentioning
confidence: 98%
“…58 It was found that overexpression of SNAIL, a key transcription factor in early EMT, in HT29 CRC cells repressed the expression of miR-192 and miR-194. It was suggestedthat the presence of SNAIL alters the complex mRNA/miRNA interactions in the early steps of metastasis and impacts the content of extracellular vesicles (EVs), which are small membrane vesicles, released from HT29 cells 59.…”
mentioning
confidence: 99%